If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -7 + 4x + 54 = x + -3 Reorder the terms: -7 + 54 + 3x + 4x = x + -3 Combine like terms: -7 + 54 = 47 47 + 3x + 4x = x + -3 Combine like terms: 3x + 4x = 7x 47 + 7x = x + -3 Reorder the terms: 47 + 7x = -3 + x Solving 47 + 7x = -3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 47 + 7x + -1x = -3 + x + -1x Combine like terms: 7x + -1x = 6x 47 + 6x = -3 + x + -1x Combine like terms: x + -1x = 0 47 + 6x = -3 + 0 47 + 6x = -3 Add '-47' to each side of the equation. 47 + -47 + 6x = -3 + -47 Combine like terms: 47 + -47 = 0 0 + 6x = -3 + -47 6x = -3 + -47 Combine like terms: -3 + -47 = -50 6x = -50 Divide each side by '6'. x = -8.333333333 Simplifying x = -8.333333333
| 6(2x-1)=10x | | 3x-7=4x+54 | | 4x+54=x-3 | | x^4-4x^3+2=0 | | 4(x-4)=42 | | -6(t-6)-t+8=1 | | 7x-13-4x=5x-8 | | x-17/5-4x-4/6=1 | | 5x-2(x-7)=3(x+1)+7 | | 2x+3(x-8)=5x-2(x-10) | | 2x+3(-8)=5x-2(x-10) | | 9x+4=7x-16 | | -4(2y-4)-y=-2(y-4) | | -5(3y-8)-y=-3(y-5) | | 5x-12=-(4x-6)+3x | | -4(6y-5)-y=-2(y-2) | | 3p+13=-29 | | 8x-3=2(x+15) | | 1/10(x+3)=1/4(2-x) | | 4m-3+7m=30 | | 2(x-5)+3=11 | | x+0.8=0.4(x+5) | | 10+2x=50 | | (7x+9)=(6+10x) | | 4x+1.3=6x-1.1 | | 2x-72+x-15=11 | | 2a^2-3a+5=0 | | 2x-1080=2x-11 | | 4(x-4)+2x=6(x+5)-46 | | 8(x-3)=4 | | x-9=-3x-9 | | 2x-72+x-15=2x-11 |